2021
DOI: 10.3390/polym13234178
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aquilaria crassna Wood as an Antifungal Additive to Improve the Properties of Natural Rubber as Air-Dried Sheets

Abstract: Fungal growth on rubber sheets confers inferior properties and an unpleasant odor to raw natural rubber (NR) and products made from it, and it causes environmental concerns. The purpose of the present work was to investigate the effects of Aquilaria crassna wood (ACW) on the antifungal, physical and mechanical properties of NR as air-dried sheets (ADS) and ADS filled with ACW. The results show that the ACW-filled ADS had an increased Mooney viscosity, initial plasticity (PO), and high thermo-oxidation plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(57 reference statements)
2
1
0
Order By: Relevance
“…In contrast, concentrated latex sheets (HA and LA) do not show fungal growth as these compounds have been removed during the concentration process. This finding is consistent with previous research that has shown that fungal growth is easily facilitated on raw rubber sheets [ 39 ]. Fungal growth on rubber sheets can lead to inferior properties and an unpleasant odor from raw natural rubber (NR) and from products made from it, and it can also cause environmental concerns.…”
Section: Resultssupporting
confidence: 94%
“…In contrast, concentrated latex sheets (HA and LA) do not show fungal growth as these compounds have been removed during the concentration process. This finding is consistent with previous research that has shown that fungal growth is easily facilitated on raw rubber sheets [ 39 ]. Fungal growth on rubber sheets can lead to inferior properties and an unpleasant odor from raw natural rubber (NR) and from products made from it, and it can also cause environmental concerns.…”
Section: Resultssupporting
confidence: 94%
“…during the concentration process. This finding is consistent with previous research that has shown that fungal growth is easily facilitated on raw rubber sheets [29]. Fungal growth on rubber sheets can lead to inferior properties and an unpleasant odor from raw natural rubber (NR) and from products made from it, and it can also cause environmental concerns.…”
Section: The Levels Of Nitrosamines In Fresh Latex and Concentrated L...supporting
confidence: 92%
“…The natural fillers used in latex foam include ash materials (Rattanaplome 2012), oil bran (Moonchai and Aimrat 2013), rice husk powder (Ramasamy et al 2013), egg shells (Bashir et al 2017), kenaf (Karim et al 2018), kenaf peel (Kudori et al 2019), sugarcane straw (Tomyangkul et al 2016), oil palm fiber (Lim et al 2018), and agarwood-waste . Researchers are additionally interested in using agarwood pellets, that are waste from a distillation process (Limhengha et al 2021), as well as agarwood waste from the distillation (Yangthong et al 2021;Faibunchan et al 2022;Nun-anan et al 2021) as fillers in natural rubber latex.…”
Section: Introductionmentioning
confidence: 99%